Charakterystyka stylistyczna XIX-wiecznych protokołów - Wojciechowska, Anna (Stylistyka, 2021)
The aim of this article is to describe style characteristics of the protocol and make an attempt to determine their hierarchy. The analysis refers to methodological postulates of Maria Wojtak conceming the study on genre style and style of non-literary texts. A set of five manuscripts of Polish societies from the second half of 19th century serves as a materiał for the article. The analysis enables to distinguish features that are determined by the structure and the pragmatics, as well as those connected with the origin of used words and expressions. Among those can be distinguished two primary style characteristics: implementation of templates and concision and five secondary: formality, use of formulas, precision, impersonality and use of directives. Repertoire of features’ exponents is connected with functioning of the protocol genre model (canonical and altemative) and the method of recording (synthetic, narrative). Apart from typical phenomena related to the communication sphere (in which the protocol is situated), common features of non-literary texts (e.g. persuasiveness, suggestiveness) are noticeable. These features are clearly conditioned by circumstances in which particular societies functioned.